The role of the school administrator in planning and implementing in-service training (LADAP) in a secondary school : a case study / Fazlinda Bahari - Bahari, Fazlinda (2013)
The research is on the implementation of Latihan Dalam Perkhidmatan (LADAP) in a secondary school in Petaling Jaya District. The study is focusing on the role of the school administrator in planning, selection of contents and also the challenges faced in implementing the program. Providing LADAP program for teachers in school is a one of the ways to upgrading teachers' professionalism. Therefore it is vital to study how proper planning and selection of contents are carried out by the school administrator to enhance teachers' skill and knowledge, thus to elevate their professionalism standard. Data for the study is gathered from teachers and school administrator using a mix method analysis. 113 teachers and 6 school administrators' were involved in this study as respondents. Qualitative data gathered from the interview session with school administrator was used as the main data analysed. Quantitative data gathered through questionnaire were processed using SPSS 16.0 software. Later on, the convergence process of both data from both sources, qualitative and quantitative methods has been done. The findings of the study shows that school administrator has done their job quite well but there is still room for improvement especially in planning more effective training program and also to improve on the process of contents selection of the program. School administrators also must take the initiatives to solve problems that are considered as challenges, whenever is possible. Even though most of the challenges are actually beyond the school administrator's authority, suggestions can be given to those responsible parties to further improvement of the program, thus achieving the objectives of the implementation of school based LADAP.